Comportamento da alface-americana sob diferentes doses de composto orgânico e lâminas de irrigação - Nunes, Kenya Gonçalves (2014)
Lettuce (Lactuca sativa L.) is one of the vegetables cultivated in several regions and nowadays it is easy to see an increase in demand for organic products by consumers, many producers decided to change and start to produce with a new method of cultivation called organic farming. Assuming that lettuce cultivation has some characteristics, like its growth and production variables, according to the different treatments, this study aimed to investigate the lettuce yield under different levels of irrigation and compost, trying to estimate the better management of irrigation and fertilization. The production of organic lettuce is held in beds under field conditions and there are many types, and some have a great acceptance what turns the studies about water and nutrient requirements more important. The irrigation system used was a drip method. Five irrigation levels were used: 50, 75, 100, 125 and 150% (W1, W2, W3, W4 and W5) of water depth needed by the crop. Another treatment was consisting of four different applications of compost, 0.0, 2.0, 4.0 and 8.0 kg m-2 (C1, C2, C3 and C4). The compost is a key in organic farming and for this experiment it was obtained from sugarcane pulp, acerola waste, cattle manure, chicken manure, MB-4 (rock powder - with Ca and Mg), phosphate and water. The experimental design was a randomized block in a split-plot with four replications scheme and irrigation depth located in the plots and the compost arranged as subplots. The results of this study led to the following conclusions: the application of water and compost as production factors allowed raising the average levels of lettuce yield of up to 38.3%, with an estimated maximum yield obtained with a level of compost equivalent to 6.3 kg m-2. It was observed a decrease lower than 6% in the average level of productivity of lettuce when the level of water was reduce by 50% the depth of irrigation applied, this result shows that this production factor it is not limiting, and it is possible to use an irrigation strategy with deficit without main contributions to the gross value of production. The average values of water productivity increased with the increase in the levels of compost according to a quadratic model, which suggests a level equivalent to 6.0 kg m-2 of compost for purposes the greater efficiency of utilization of water by lettuce. Considering the current price of a kilogram of lettuce to R$ 2.00 and the results of the compost use efficiency, the cost of a compost tonne must be less than R$ 90.00 to enable the application of this input. The best economically level of compost, like an optimal value, practically did not change with vary in water quantity and the relationship between the price of the compost and the product price ranging between 90 and 110.